TINJAUAN YURIDIS PAJAK DAERAH MENURUT UNDANG-UNDANG NOMOR 28 TENTANG PAJAK DAERAH DAN RETRIBUSI DAERAH : STUDI KASUS: PEMERINTAH KOTA TANGERANG - Atikah, Atik (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2021)
The euphoria of regional autonomy sometimes causes parties in the regions to be free in making various regional regulations as well as local taxes and levies. Law Number 28 of 2009 concerning regional taxes and regional levies is one form of implementing the principles of regional autonomy legislation for regional governments, as well as regional finances, especially for the creation of effectiveness and efficiency in the regions. In the case that the method of collection and the amount of tariffs for all types of regional taxes is stipulated through a regional regulation or regional regulation, therefore, prior approval must be obtained from the respective Regional People’s Representative Council concerned in accordance with the implementation of the principle of democracy in a regional regulation containing such regional taxes, pay attention to the directions from the central government through the provisions contained in Law Number 34 of 2000 and Government Regulation Number 65 of 2001, particularly in terms of determining the amount of tariff and of each type of regional tax in each region so that it can be prevented. a tariff war between regions which can actually be detrimental to the regions themselves